READING CULTURE: THE SITUATION AMONG YOUNG PEOPLE (Eureka Journal of Education & Learning Technologies, 2025)
This article examines the importance of reading culture in the intellectual and spiritual development of young people. In the era of rapidly developing information technologies, many young individuals spend a significant amount of their time on smartphones, the internet, and social media platforms. As a result, the habit of reading books is sometimes declining among youth. The article analyzes the role of reading in developing critical thinking, enriching vocabulary, and shaping worldview. It also discusses the main factors influencing young people’s interest in books and suggests several ways to promote reading culture among the younger generation.
Keywords: Reading culture, youth, books, education, intellectual development, technology, knowledge, social media.